The biocontrol endophytic bacterium Pseudomonas fluorescens PICF7 induces systemic defense responses in aerial tissues upon colonization of olive roots - Gómez-Lama Cabanás, Carmen; Schilirò, Elisabetta; Valverde-Corredor, Antonio; Mercado-Blanco, Jesús (Frontiers in Microbiology, 2014)
Pseudomonas fluorescens PICF7, a native olive root endophyte and effective biocontrol agent (BCA) against Verticillium wilt of olive, is able to trigger a broad range of defense responses in root tissues of this woody plant. In order to elucidate whether strain PICF7 also induces systemic defense responses in above-ground organs, aerial tissues of olive plants grown under non-gnotobiotic conditions were collected at different time points after root bacterization with this endophytic BCA. A suppression subtractive hybridization (SSH) cDNA library, enriched in up-regulated genes, was generated. This strategy enabled the identification of 376 ESTs (99 contigs and 277 singlets), many of them related to response to different stresses. Five ESTs, involved in defense responses, were selected to carry out time-course quantitative real-time PCR (qRT-PCR) experiments aiming to: (1) validate the induction of these genes, and (2) shed light on their expression pattern along time (from 1 to 15 days). Induction of olive genes potentially coding for lipoxygenase 2, catalase, 1-aminocyclopropane-1-carboxylate oxidase, and phenylananine ammonia-lyase was thus confirmed at some time points. Computational analysis also revealed that different transcription factors were up-regulated in olive aerial tissues (i.e., JERF, bHLH, WRKY), as previously reported for roots. Results confirmed that root colonization by this endophytic bacterium does not only trigger defense responses in this organ but also mounts a wide array of systemic defense responses in distant tissues (stems, leaves). This sheds light on how olive plants respond to the “non-hostile” colonization by a bacterial endophyte and how induced defense response can contribute to the biocontrol activity of strain PICF7.